Penyuluhan dan Deteksi Dini Anemia menuju Generasi Berkualitas pada Mahasiswa Kebidanan - Marlynda Happy Nurmalita Sari; Dina Dewi Anggraini (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: The prevalence of anemia in adolescent girls in Indonesia is still high at 57.1%. As a result of anemia is adolescent learning achievement can decrease, work productivity decreases and body immunity decreases so that the body is easily infected. Long-term effects of anemia in adolescent girls can occur complications of pregnancy and even the risk of maternal and perinatal death. Purpose of this studi is provide counseling and early detection of anemia to Midwifery students as an effort to make them aware in preventing and overcoming anemia. Methods: The target of this activity is 132 students of the Blora Midwifery Diploma Program. This activity is carried out by providing information or knowledge in the form of counseling to students about anemia and followed by history and physical examination. Only students who showed signs and symptoms of anemia who were tested for HB levels were 30 students. Results: Early detection of 30 students there were 53.3% who were not anemic and 46.7% were anemic. Most of the students' menstruation period is 6-7 days which is 73.3%. While the results of counseling some students already understand about anemia. Conclusion: Of the 132 students only 30 showed signs and symptoms of anemia. Hb examination results are almost the same between respondents who are anemic and not anemic. It is hoped that the results of community service activities can be used as an illustration of the incidence of anemia in Midwifery students so that efforts can be made to prevent and manage anemia. Provide motivation and awareness to students to consume nutritious and iron-containing foods or to consume extra blood tablets.